Association between motor competence, sex, age, and risk of obesity in children from the austral zone of Chile - Díaz Alvarado, Mauricio Andrés; Estevan, Isaac; Salvo-Garrido, Sonia; Carcamo-Oyarzun, Jaime (My University, 2025)
Motor competence (MC) is crucial for promoting an active lifestyle. Endogenous factors such as age, sex, and weight status influence its development. The prevalence of physical inactivity and obesity is concerning, especially in the most southern area of Chile, which is characterised by its isolated geography and extreme climate. This study aimed to determine the level of motor competence in children from the southernmost region of Chile at the onset of primary education and to analyze the association between MC, sex, age, and risk of obesity. The study included 830 schoolchildren (55.7% girls, age M = 7.51) from 1st and 2nd grades. Motor competence was assessed using the MOBAK 1-2 test, and the risk of obesity was measured using the waist-to-height ratio (WHtR). Results showed that motor competence levels were generally between "needs improvement" and "acceptable performance." Structural equation modelling revealed significant associations between motor competence and age (object control only), sex (boys with object control and girls with self-movement), and WHtR (self-movement only). This study highlights the importance of considering these factors to improve the motor competence of children from this region.
Keywords: motor skills; motor development; physical education; weight status